Dialecte et culture régionale dans la réforme de l’école italienne en 1923 - Maurizio Coppola (Lengas)
The "Gentile" Reform, of 1923, has introduced for the first time in Italy the teaching of regional culture and dialect in elementary school. These new subjects, nevertheless, were part of the idealistic project of Giovanni Gentile and Giuseppe Lombardo Radice to build an "Italian identity" through the construction of a national education. For this reason (ici, si les dialects et la culture locale non pas cesser d'être des instruments importants, tu peux mettre « Ever since »), dialects and local culture are considered necessary instruments to enhancing a sense of national unity and for learning the Italian language.